Combination effect of gallic acid and cisplatin on ros and GSH production of cervical cancer cells, hela - Nazri, Batrisyia Mohd (2023)
Cervical cancer is one of the leading causes of death among women worldwide. Unfortunately, most of the available cancer treatments reported to cause side effects. Therefore, patients turn to alternative treatments by utilizing natural products. Gallic acid (3,4,5‑trihydroxy benzoic acid; GA), a plant‑derived natural phenolic compound, has been reported to prevent the development and progression of various types of cancers. Anticancer activities of GA were reported due to regulation of reactive oxygen species (ROS) and glutathione (GSH) at the cellular level. However, its mechanism of action is still unclear. Thus, this study aimed to evaluate the regulations of ROS and GSH on the combination of cisplatin and GA in HeLa cells at 24 and 48 hours treatment period at IC50 concentration. ROS levels, including H2O2 concentrations were measured in HeLa cells as these variations appear to influence cervical cancer's vulnerability to cisplatin treatment over both the 24-hour and 48-hour intervals. Moreover, GSH levels were measured in treated HeLa cells as it helps to provide information about the intricate balance between the body's attempts to counter oxidative stress and the response of cervical cancer cells to the damage caused by the treatment. The results revealed that the combination of cisplatin and GA led to distinct patterns of ROS production for both the 24-hour and 48-hour intervals. This highlights the substantial influence of ROS levels on the treatment efficacy. Additionally, H2O2 levels was elevated during the 48-hour period when cisplatin and GA were combined. This increase aligned with the initiation of apoptosis, highlighting the time-dependent nature of H2O2 levels production, as the combination treatment demonstrated increased concentration after 48 hours. Moreover, during the 48-hour treatment